Evaluation of stationary phase and bile stress related protein spots in Lactobacillus fermentum NCDC 400 by 2-DE method - Behare, Pradip Vishnu (Indian Journal of Dairy Science, 2015)
The aim of the study was to evaluate stationary phase in L. fermentum NCDC 400 and observe total number of protein spots expressed in control and bile treated samples of NCDC 400. The early stationary phase for NCDC 400 was 9 h based on calculation of Mean Growth Rate Constant (K=0.011). L. fermentum NCDC 400 count was decreased as the concentration of bile increased from 0.3 to 1.5%. For analysis of protein spot by 2-DE method 1.2% bile concentration was selected as it was less damaging to the cell. Among the three methods used for extraction of proteins from NCDC 400, sonication method yields better proteins (1503.77 Âµg/ml) to study proteome by 2-DE. Total of 240 and 323 protein spots were respectively observed in control (without bile treatment) treated samples (1.2% bile) by 2-DE technique. Additional 83 protein spots produced by NCDC 400 indicated that the cell trying to overcome the damaging effect of bile. Â